2013
DOI: 10.5152/balkanmedj.2012.097
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Left Ventricular Mass Index and Calcium Metabolism in Patients with Essential Hypertension

Abstract: IntroductionLeft ventricular hypertrophy (LVH) is an independent risk factor for cardiovascular morbidity and mortality in hypertensive patients (1-3). Even though some results regarding the relationship between hypertrophy and the severity of hypertension are contradictory, a number of studies have reported that the prevalence of hypertrophy increases with the severity of hypertension (4, 5).Essential hypertension is a multifactorial condition affecting a large percentage of the adult Turkish population (33.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
4
3
0
1
Order By: Relevance
“…This is not surprising according to [17] that elevated blood pressure corresponds with high LVMI. Moreover, GATAN identifies more subtle relations between lab results and LVMI, including potassium, vitamin D, calcium, diabetes status, bun, renin et al These top-ranked features accord with previous researches ([15, 18, 19]), demonstrating that feature ranking by analyzing the learned weights is a reasonable heuristic for interpreting deep neural networks.
Fig.
…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…This is not surprising according to [17] that elevated blood pressure corresponds with high LVMI. Moreover, GATAN identifies more subtle relations between lab results and LVMI, including potassium, vitamin D, calcium, diabetes status, bun, renin et al These top-ranked features accord with previous researches ([15, 18, 19]), demonstrating that feature ranking by analyzing the learned weights is a reasonable heuristic for interpreting deep neural networks.
Fig.
…”
Section: Resultssupporting
confidence: 78%
“…However, the Pearson correlation between LVMI and calcium is 0.00 for the entire dataset, -0.10 for LVMI <120. In previous studies [15, 16], it was shown that patients with LVH have strong positive correlation with serum calcium level compared to those without LVH. Our observations are consistent with these findings.…”
Section: Resultsmentioning
confidence: 99%
“…There is much debate in current medical literature regarding the association of cholecalciferol deficiency and LVH in essential hypertension from various countries. [10][11][12] The finding of low serum cholecalciferol shows highly negative correlation that was in descending order as shown in Table-II, the finding is in agreement with a recent study from Pakistan. 8 The serum PTH and serum calcium were found elevated in LVH cases, this is being highly consistent with previous studies.…”
Section: Table-iii Correlation Of Left Ventricular Hypertrophy In Casessupporting
confidence: 90%
“…Calcium homeostasis impairment also is a prominent feature in the transition from compensatory hypertrophy to heart failure [ 54 ]. In additional, hemodynamics can be altered by variations in serum calcium through changes in left ventricular stroke volume and output [ 28 ]; and essential hypertension can alter calcium metabolism which in turn provokes the development of myocardial hypertrophy [ 57 ].…”
Section: Discussionmentioning
confidence: 99%